2019
DOI: 10.3390/agronomy9100606
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Cultivating Dry Season Maize along a Hydrological Gradient of an Inland Valley in Uganda

Abstract: Inland valley wetlands with higher soil moisture than surrounding uplands offer a yet unexplored opportunity for increasing maize production in East Africa. For three consecutive years, we conducted field experiments to assess the potential of an inland valley in Central Uganda for producing dry season maize. A randomized complete block design was used with six treatments including farmer’s practice, unfertilized control, organic and inorganic fertilizer applications at high and low rates. These were repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…[ 75 ] suggested that relaxing liquidity constraints could help to encourage farmers’ adaptation through the implementation of soil, water and land management strategies; thereby, positioning east Africa for food sufficiency in the face of the current global food crisis. [ 76 ] noted that intensive manuring with a combination of green and poultry manure produced high yields of maize in central Uganda that were comparable to those with mineral fertilizers. [ 77 ] demonstrated that households in Kenya adapting to climate change and climate variability through uptake of technologies such as early planting, use of improved crop varieties, and crop diversification produced 4877 kilograms of maize yield equivalent / hectare per year against 3238 kilograms of maize yield equivalent / hectare per year for households that did not adapt (a 33.6% difference between the two groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 75 ] suggested that relaxing liquidity constraints could help to encourage farmers’ adaptation through the implementation of soil, water and land management strategies; thereby, positioning east Africa for food sufficiency in the face of the current global food crisis. [ 76 ] noted that intensive manuring with a combination of green and poultry manure produced high yields of maize in central Uganda that were comparable to those with mineral fertilizers. [ 77 ] demonstrated that households in Kenya adapting to climate change and climate variability through uptake of technologies such as early planting, use of improved crop varieties, and crop diversification produced 4877 kilograms of maize yield equivalent / hectare per year against 3238 kilograms of maize yield equivalent / hectare per year for households that did not adapt (a 33.6% difference between the two groups).…”
Section: Discussionmentioning
confidence: 99%
“…[75] suggested that relaxing liquidity constraints could help to encourage farmers' adaptation through the implementation of soil, water and land management strategies; thereby, positioning east Africa for food sufficiency in the face of the current global food crisis. [76] noted that intensive manuring with a combination of green and poultry manure produced high yields of maize in central Uganda that were comparable to…”
Section: Plos Onementioning
confidence: 99%